Social Media Engagement With Cancer Awareness Campaigns Declined During the 2016 U.S. Presidential Election. Issue 4 (16th November 2017) - Vraga, Emily K.; Radzikowski, Jacek R.; Stefanidis, Anthony; Croitoru, Arie; Crooks, Andrew T.; Delamater, Paul L.; Pfoser, Dieter; Jacobsen, Kathryn H.
Abstract : Cancer awareness campaigns compete with other health and social issues for public attention. We examined whether public engagement with breast cancer and prostate cancer declined in 2016 during the U.S. presidential election compared to 2015 on Twitter and Google Trends. We found that attention to breast cancer and prostate cancer declined in 2016 before the election as compared to 2015 in Twitter posts and Google searches. The findings suggest that cancer information seeking behavior, passive exposure to health communication, and active participation in social media about cancer all decreased during the peak weeks of the 2016 election season. Future health promotion initiatives and information dissemination efforts will benefit from monitoring the major issues garnering social media attention and then adjusting their timing or communication strategies to ensure that public engagement with their key policy messages remains strong when emerging news stories capture public interest.